TAM dan UTAUT dalam penerapan e-filing untuk mengukur kepatuhan wajib pajak di masa pandemi covid-19 - Rakhmawati, Henny; Hariyanti, Tiwuk Puji (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of perceived usefulness, perceived convenience, and social influence of the implementation of e-filing on taxpayer compliance during the Covid-19 pandemic. Sampling using a convenience sampling method on taxpayers in the area of ​​DJP III East Java. This study uses the Partial Least Square analysis model. The results show that, firstly, the perception of the usefulness of using e-filing has a positive effect on tax compliance during the Covid-19 pandemic. Furthermore, the social influence of the use of e-filing has a positive effect on tax compliance. The final results show that the perceived ease of use of e-filing has an effect on tax compliance during the Covid-19 pandemic. These three findings support the theory of planned behavior that a person's intentions will be stronger if the individual considers three factors, namely attitudes, perceived behavioral control and subjective norms.